PENGARUH STRESSOR TERHADAP KINERJA PEGAWAI (Studi Pada 16 Kantor Urusan Agama Di Kabupaten Banjar) - Muhammad Laili Sanusi; Dahniar (JWM (JURNAL WAWASAN MANAJEMEN), 2014)
The purpose of this research to determine and analyze the influence of stressor from environment, organization and personal in simultaneosly or partially to the employee performance in the Office of Religious Affairs Banjar Regency. The research method used in this research is quantitative method. The analysis unit of this research is employees in the Office of Religious Affairs in Banjar Regency. Collecting data using questionnaires distributed to 55 respondents. Determination of samples using non probability sampling techniques and data analysis using multiple linear regression. The results revealed stressor from the environment, stressor from the organizational and stressor from personal has influence positive and significant in partially or simultaneously to employee performance in the Office of Religious Affairs in Banjar Regency. Stressor from the organizational has the most dominant influence to the employee performance in the Office of Religious Affairs at Banjar Regency